Analysis Of Leadership Style And Technology Application Using Work Discipline As A Mediation Variable On Employee Achievement At Padang Cement Company - Isyraqi Zihadyan; Yulihasri; Laura Syahrul (Jurnal Mantik, 2022)
The purpose of this study was to determine and analyze the influence of leadership style and the application of technology using work discipline as a mediating variable on employee achievement at PT. Padang Cement. Achievement is an important thing that must be considered by company management in managing company resources or employees. Aspects that affect employee achievement are leadership style, application of technology to employee achievement, and perceived work discipline by employees. In this case, the researcher focuses on the perceived work discipline variable as a mediating variable that links leadership style and application of technology to employee achievement. The population in this study were employees at PT Semen Padang with a sample of 162 people by using kretjie table. The analytical method used is descriptive statistical analysis and factor description analysis using SmartPLS 3.0 software. The results showed that leadership style had a negative and significant effect on work discipline; the application of technology has a positive and significant impact on work discipline; leadership style, application of technology, and work discipline have a significant impact on employee achievement; work discipline as a mediating variable has an effect and fully mediates on leadership style on employee achievement and the application of technology on employee achievement also partially mediates.